Epoxidation of soybean oil by using Na2WO4/H2O2/H3PO4 based catalyst. Issue 3 (25th April 2022) - Thuy, Nguyen Thi; Liem, Nguyen Thanh; Duc, Vu Minh
Abstract: This paper presents epoxidation using a Na2 WO4 /H2 O2 /H3 PO4 ‐based complex catalyst, which is formed from in aqueous phase in situ during the process. The success of the epoxidation was demonstrated by the FTIR investigation results. A variety of factors such as reaction conditions, reactant and composition of catalyst system that influence the epoxidation reaction was examined through the oxirane content, yield, conversion, and catalyst selectivity. In which, the rate of addition of reactants as well as the catalytic complex is one of the influencing factors studied. The optimal ratio of the reactants as well as of the components of the catalyst system was found. The reaction was caried out at 60°C for one hour. The results show that 91 % of the double bonds were broken and 87.7 % of the double bonds were converted to epoxide groups, so the epoxidized oil has 6.7 % oxirane content and the catalytic selectivity reached 96.3 %.